A standardized extract of Centella asiatica (ECa 233) prevents temporomandibular joint osteoarthritis by modulating the expression of local inflammatory mediators in mice - Nattapon ROTPENPIAN; Tawepong ARAYAPISIT; Atitaya ROUMWONG; Narawut PAKAPROT; Mayuree TANTISIRA; Aree WANASUNTRONWONG (Journal of Applied Oral Science, 2021)
Abstract Objectives To investigate the effect of a standardized extract of Centella asiatica (ECa 233), which has anti-inflammatory properties, on the local expression of the transient receptor potential vanilloid 1 (TRPV1), the acid-sensing ion channel subunit 3 (ASIC3), and the calcitonin gene-related peptide (CGRP) in the temporomandibular joint (TMJ) structure 21 days after injecting the TMJ with complete Freund’s adjuvant (CFA). Methodology A mouse model was induced by analyzing the CFA-injected TMJ on days 7, 14, and 21. We assessed TMJ histology by the osteoarthritis cartilage grade score. Then, we observed the effect of different ECa 233 concentrations (30, 100, and 300 mg/kg) and of 140 mg/kg ibuprofen doses on TRPV1, ASIC3, and CGRP local expression on day 21. Results Osteoarthritis cartilage scores were 1.17±0.37 and 3.83±0.68 on days 14 and 21, respectively, in the CFA group (n=5). On day 21, TRPV1, ASIC3, and CGRP expression significantly increased in the CFA group. In the ibuprofen-treated group, TRPV1 expression significantly decreased, but ASIC3 and CGRP showed no significant difference. All ECa 233 doses reduced TRPV1 expression, but the 100 mg/kg ECa 233 dose significantly decreased ASIC3 expression. Conclusions TRPV1, ASIC3, and CGRP expression increased in mice with TMJ-OA on day 21. All ECa 233 and ibuprofen doses inhibited pathogenesis by modulating the local expression of TRPV1 and ASIC3. Therefore, ECa 233 was more effective than ibuprofen.